2020
DOI: 10.3389/fnhum.2020.584704
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Processing Differences Correlate With Autistic Traits in Males

Abstract: Autism spectrum disorder (ASD) has high prevalence among males compared to females but mechanisms underlying the differences between sexes are poorly investigated. Moreover, autistic symptoms show a continuity in the general population and are referred to as autistic traits in people without an ASD diagnosis. One of the symptoms of ASD is sensory processing differences both in sensitivity and perception. To investigate sensory processing differences in autistic traits, we examined auditory and visual processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
(81 reference statements)
1
6
0
Order By: Relevance
“…The discrepancy in our findings with those of Tavassoli et al, ( 2014 ) highlight that self-report and psychophysical assessments of sensory perception are not necessarily congruent and are possibly testing different constructs. The same could be said when comparing our results to the studies which have compared autistic males and autistic females on sensory reactivity (Aykan et al, 2020 ; Bitsika et al, 2020 ; Kumazaki et al, 2015 ; Lai et al, 2011 ; Osório et al, 2021 ), which speaks to the affective appraisal of sensory stimuli rather than low-level perception. Future studies comparing sensory differences between autistic males and autistic females should consider including both measures of sensory perception and sensory reactivity.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The discrepancy in our findings with those of Tavassoli et al, ( 2014 ) highlight that self-report and psychophysical assessments of sensory perception are not necessarily congruent and are possibly testing different constructs. The same could be said when comparing our results to the studies which have compared autistic males and autistic females on sensory reactivity (Aykan et al, 2020 ; Bitsika et al, 2020 ; Kumazaki et al, 2015 ; Lai et al, 2011 ; Osório et al, 2021 ), which speaks to the affective appraisal of sensory stimuli rather than low-level perception. Future studies comparing sensory differences between autistic males and autistic females should consider including both measures of sensory perception and sensory reactivity.…”
Section: Discussionsupporting
confidence: 71%
“…There are also very few studies which have directly compared sensory features between autistic males and autistic females using purpose-built measures. Those that exist have typically compared ‘sensory reactivity’ (Aykan et al, 2020 ; Bitsika et al, 2020 ; Kumazaki et al, 2015 ; Lai et al, 2011 ; Osório et al, 2021 ), which describes the presence or absence of affective/behavioural reactions to sensory input. The results of studies comparing sensory reactivity between autistic males and autistic females are mixed.…”
Section: Introductionmentioning
confidence: 99%
“…Further, additional information about these subjects such as their age or ADOS scores was not available. Prior studies have suggested that sensory processing differences are associated with level of function (Klintwall et al, 2011, Aykan et al, 2020. Future prospective studies will be needed to validate the subgroups identi ed in this study and to expand our understanding of the associated clinical features for each of these subgroups.…”
Section: Limitationsmentioning
confidence: 77%
“…Sutherland et al ( 2017) identified autistic females as reporting significantly higher rates of sensory sensitivity in relation to the specific element of taste. Visual sensitivity has also been correlated with autistic traits in females, whereas auditory sensitivity was correlated with autistic traits in males (Aykan et al, 2020). A trend towards autistic boys displaying more behaviours associated with unusual interests in smell, texture, and/or sound (although defined as 'sensory seeking' in the study) and visual interests (e.g., visual inspection, looking at objects from certain angles, bringing objects close to eyes, visual stimulatory behaviours) during recorded caregiver-child interaction (CCX) has been reported by Harrop et al (2015).…”
Section: Key Findings From Narrative Synthesismentioning
confidence: 99%